Hydrogen permeation behavior and mechanism of Cr2O3/Al2O3 bipolar oxide film under plasma discharging environment. (10th August 2017) - Xin, Zhiyuan; Yin, Xiaoran; Ling, Yunhan; Zhang, Zhengjun; Liu, Xiao; Liang, Hao; Deng, Xiukun
Abstract: To improve the thermal stability between aluminide and stainless steel substrate and obtain thermodynamically stable phase of alpha-Al2 O3, a new Cr2 O3 /Al2 O3 bipolar oxide barrier was proposed, in which metallic Al was sputtered on the preoxidation coating of electroplated chromium and then oxidizing by oxygen plasma. It was found that Cr2 O3 film exhibits P-type semiconducting properties while Al2 O3 acts as N-type. Hydrogen discharging plasma was used to simulate the in-pile hydrogen permeation. Raman spectra and atomic force microscopy (AFM) were employed to analyze phase structure and surface morphology. Electrochemical impedance spectroscopy and Mott–Schottky were utilized to qualitatively evaluate effective thickness and the integrity for the oxide film. The depth profile and surface chemical states of involving elements were analyzed by auger electron spectroscopy (AES) and X-ray photoelectron spectroscopy (XPS), respectively. The result shows that Cr2 O3 /Al2 O3 bipolar oxides have improved hydrogen permeation resistance and would be a potential candidate for barrier application. Highlights: A new kind of Cr2 O3 /Al2 O3 bipolar hydrogen permeation barrier is proposed. Oxygen plasma oxidization method was used to obtain dense passive film. The bipolar oxide was proved to be effective in hydrogen resistance.